Clinical Evaluation of the Peroral Cholangioscopy Using a New Videoscope. Issue 4 (1999) - Igarashi, Yoshinori; Ukita, Takeo; Inoue, Hirokazu; Ishiguro, Jun; Ogawa, Satoshi; Satou, Masahiro; Maetani, Iruru; Sakai, Yoshihiro
Abstract : Peroral cholangioscopy (PCS) has been performed in 22 cases using XCHF-B200 (Olympus Optical Co.) since June 1995 and in 77 cases using CHF-B20 (Olympus Optical Co.) after EST from Jan. 1989. XCHF-B200 has a longer rigid portion of distal end and a smaller channel diameter than CHF-B20. The successful rate of PCS using XCHF-B200 (82%) was lower than that of CHF-B20 (89%). The vascular pattern and fine vertical groove of the bile duct mucosa were shown more clearly on the photographs obtained with XCHF-B200 than those obtained with CHF-B20. However, not enough biopsy specimens could be obtained because the channel diameter of XCHF-B200 was rather small. If the length of rigid portion and biopsy channel of XCHF-B200 are improved, PCS using XCHF-B200 will be more useful for the diagnosis of bile duct disorders.